Perlindungan Hukum Usaha Mikro, Kecil, Dan Menengah Melalui Fasilitasi Sertifikasi Halal Produk Pangan (Studi terhadap Praktek di Kalimantan Tengah) - Tri Hidayati; Erry Fitrya Primadhany (Jurnal Hukum IUS QUIA IUSTUM, 2021)
Halal certification for products is the obligation of all business actors (Article 4 UUJPH). MSMEs also need to enjoy the facility of halal certification from local governments, but the number of halal-certified UMKM products in Central Kalimantan tends to be low. This research raises two problems, first, how to facilitate the implementation of halal certification for UMKM products in Central Kalimantan. Second, what is the role of the Central Kalimantan regional government in providing legal protection to MSMEs by facilitating halal certification of food products. This is an empirical or socio-legal legal research that uses primary data and secondary data. The results of this study concluded: 1. The facilitation of halal certification for UMKM products in Central Kalimantan was carried out in the form of, first, socialization and training of MSMEs regarding non-formal halal certification; Second, the budget policy for the cost of halal certification for new MSME entrepreneurs 2018-2019 at the Ministry of Trade and Industry of Central Kalimantan Province, however, is not a priority and has very little quota compared to the number of MSMEs; Third, the realization of certification fee assistance is carried out every year but information and coordination between the Provincial and Regency / City Governments is still weak as a result of limited access to MSMEs. 2. The Central Kalimantan government has played a role in providing preventive legal protection for MSMEs through the facilitation of halal certification in the sector of Industry, Ministry of Industry and Industry of Central Kalimantan and regencies / cities, but this has not been maximally implemented.